Papers of Mackendrick Rich - Rich, Mackendrick Charles William, 1903- (1921)
Approximately sixty letters, newsclipping, radio permits and licences relating to the setting up of wireless stations in Papua and New Guinea by M. Rich. Approximately 30 letters, 20 monthly reports, photographs, Government Gazettes, a map and other papers relating to the administration and Rich's positions as District Officer and Assistant Director between 1939-1950. Also includes handwritten diary (1951) of journey and investigations by Rich and papers in English and native language on Papua and New Guinea. Photocopies are of official papers regarding Milne Bay Division Inspection 1951 and lists of offices in Public Service.
Manuscript reference no.: MS 3879.
Originals and photocopies.
Guide to collections of manuscripts relating to Australia
Some originals in private ownership.
Rich was a public servant in the Papua and New Guinea administration between 1924-1951. He was stationed in various districts of South Papua andthe Trobriand Islands and held the positions of Patrol Officer, District Officer, Assistant Resident magistrate and finally Acting Assistant Director of the Department of District Services and Native Affairs.
Keywords: Rich, Mackendrick Charles William, -- 1903- -- Archives; Papua New Guinea -- Department of District Services -- Officials and employees -- Archives; Telephone, Wireless -- Stations; Papua -- Officials and employees -- Archives; Papua New Guinea -- Officials and employees -- Archives; Papua New Guinea -- Politics and government -- To 1975.; Papua New Guinea -- Languages; Public servants; Patrol officers